The Use of Metrics and KPIs in Data-Driven Improvement of Traffic Safety - Repas, Ana; Marič, Miha (Prometna varnost v lokalnem okolju: problemsko-učno sodelovanje z Intermatic d.o.o., 2026)
Traffic safety remains an important societal challenge despite the development of digital traffic solutions and the increasing availability of traffic-related data. In practice, a gap exists between extensive data collection and the systematic use of such data in decision-making processes. The purpose of this study is to examine the role of metrics and key performance indicators (KPIs) in data-driven improvement of traffic safety within the context of digital traffic solutions. The research is based on a case study of a company developing traffic monitoring systems. It includes an analysis of the types of collected data, their transformation into metrics and key performance indicators, and an assessment of the impact of data quality on the reliability of decision-making processes. The findings indicate that the effectiveness of data-driven management depends not only on the quantity of collected data but primarily on their quality, structured processing, and a clear connection between metrics, key performance indicators, and strategic objectives. The study contributes to bridging the gap between theoretical concepts of performance measurement and their practical application in the context of smart mobility, while also providing a basis for a more systematic operationalization of traffic data to support decision-making at the local level.